Pathological processes of the cervix in lichen sclerosus of the vulva - Delya F. Porsokhonova; Avaz Sh. Inoyatov; Nurjanar N. Ilesova (Vestnik Dermatologii i Venerologii)
Background. Taking into account the possible unity of etiopathogenetic mechanisms causing dysplastic processes of the cervix and vulva, one of the factors leading to synchronous damage to the cervix and external genitalia may be microbial-viral associations from the group of STIs.